Immune complexes and abnormal liver function in haemophilia. Issue 12 (December 1977) - McVerry, B A; Voke, J; Mohammed, I; Dormandy, K M; Holborow, E J
Abstract : Abnormal 125I-Clq-binding activity was found in the sera of 94% of 55 haemophiliacs. Sera from 66% of these patients inhibited macrophage uptake of labelled aggregated human IgG in a competitive radiobioassay. These results suggest that large molecular weight immune complexes are present in these sera. Analysis of the precipitates obtained directly from the sera by addition of 4% polyethylene glycol showed either a mixture of IgG and IgM or IgM alone. There was poor correlation between the radiobioassay results and the Clq-binding activities in the whole group of 55 patients, suggesting a heterogeneous population of complexes. Nevertheless, a significant correlation was found between Clq-binding activities and the radiobioassay results in seven patients with antibodies to factor VIII, suggesting a homogeneous population of complexes. There was poor correlation between the level of immune complexes and the amount of replacement therapy the patient had received in the previous six months. Abnormal liver function tests were found in 55% of the patients studied but there was poor correlation between these abnormal levels and the Clq binding activities and radiobioassay results. Only two patients had clinical evidence of liver disease.